RETRACTED: Algorithm for systematizing information about scientific activities in the environmental education system - Katalazhnova Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001